2015
DOI: 10.1093/ndt/gfv255
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and mild chronic kidney disease persist following severe haemolytic uraemic syndrome caused by Shiga toxin-producingEscherichia coliO104:H4 in adults

Abstract: Although shiga toxin-producing Escherichia coli (STEC)-HUS induced by O104:H4 was a life-threatening acute disease, follow-up showed a good recovery of organ function in all patients. Whereas kidney function recovered even after longer duration of dialysis, chronic hypertension developed after severe HUS with neurological symptoms and could not be prevented by the extended therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…As in our patients, it has been previously observed that the GFR can improve or deteriorate over time after HUS [20,21]. Similar to the results of Rosales et al and our results, 2 of 45 (4%) adult patients from the 2011 outbreak from a single center had increased creatinine after 1 year of follow-up [22]. However, decreased eGFR < 90 mL/min calculated from cystatin C was found in Figure 3.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As in our patients, it has been previously observed that the GFR can improve or deteriorate over time after HUS [20,21]. Similar to the results of Rosales et al and our results, 2 of 45 (4%) adult patients from the 2011 outbreak from a single center had increased creatinine after 1 year of follow-up [22]. However, decreased eGFR < 90 mL/min calculated from cystatin C was found in Figure 3.…”
Section: Discussionsupporting
confidence: 91%
“…Substantial variation between the different studies might also be due to the different definitions of proteinuria applied. Again adults affected during the outbreak showed similar results, with albuminuria in 27% of the cases at 1-year follow-up [22]. Although proteinuria in patients after HUS is more common compared with the normal population and proteinuria is associated with impaired kidney function, it is not necessarily a measure for poor outcome.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The overall increased systolic and diastolic blood pressure places the PNA animals in the range of uncomplicated stage I hypertension (between 140/90 to 150/99 mmHg). 71 , 72
10.1080/19490976.2018.1441664-F0004Figure 4.Radiotelemetry Blood Pressure, Heart Rate, and Locomotor Activity. Radiotelemetry analysis was performed for moving averages every hour for 28 hours with standard error calculated for each hour.
…”
Section: Resultsmentioning
confidence: 99%
“…38 , 39 Bacteria from the family Enterobacteriaceae , particularly Escherichia coli , have been associated with increased systemic lipopolysaccharides 136 , increased risk of obesity, inflammation, reduced glomerular filtration rate, increased serum cystatin C and insulin resistance. 71 , 137 , 138 …”
Section: Discussionmentioning
confidence: 99%